Ion channel trafficking implications in heart failure - Reisqs, Jean-Baptiste; Qu, Yongxia Sarah; Boutjdir, Mohamed (Frontiers in Cardiovascular Medicine, 2024)
Heart failure (HF) is recognized as an epidemic in the contemporary world, impacting around 1 to 2% of the adult population and affects around 6 million Americans. HF remains a major cause of mortality, morbidity, and poor quality of life. Several therapies are used to treat and to improve survival for patients, but although these substantial improvements in treating HF, the incidence of HF is increasing rapidly, posing a significant burden to human health. The total cost of care for HF is 69.8 billion in 2023, warranting a better understanding of the mechanisms involved in HF. Among the most serious manifestations associated with HF is arrhythmias due to electrophysiological changes within the cardiomyocyte. Among these electrophysiological changes, disruptions in sodium and potassium currents function and trafficking, as well as calcium handling all of which impact arrythmias in HF. The mechanisms responsible for the trafficking, anchoring, organization, and recycling of ion channels at the plasma membrane seems to be a significant contributor to ion channels dysfunction in HF. Variants, microtubules alterations or disturbance of anchoring proteins leads to ion channel trafficking defect and alteration of the cardiomyocyte's electrophysiology. Understanding the mechanisms of ion channels trafficking could provide new therapeutic approaches for the treatment of HF. This review provides an overview of the recent advances of the ion channel trafficking in HF.